Respuesta :
Answer:
Step-by-step explanation:
Take out the common factor from the first and second terms and again from the 3rd and fourth terms.
x^2(x + 2) - 9(x + 2)
Take out x + 2 from around the minus sign.
(x + 2)(x^2 - 9)
Factor x^2 - 9 which will come out to the difference of squares.
(x + 2)(x + 3)(x - 3)
This is how it factors.
You could also use synthetic division if you know how it works.
-2 || 1 2 -9 -18
-2 0 18
====================
1 0 -9 0
This gives you (x + 2)(x^3 - 9) just as before.
Answer:
(x-2)(x-3)(x+3)are the factors of the given expression.
Step-by-step explanation:
We have given the expression:
x³ +2x² -9x -18
And we have given that -2 is the zero of the given expression.
We have to find the other factors of this expression.
Taking common from the given expression we get,
x³ +2x² -9x -18 = x²(x-2)-9(x-2)
Taking (x-2) common from x²(x-2)-9(x-2) we get,
x²(x-2)-9(x-2) = (x-2)(x²-9)
As we know that,
(x²-9) = (x-3)(x+3)
(x-2)(x²-9) = (x-2)(x-3)(x+3)
(x-2)(x-3)(x+3)are the factors of the given expression.